Komunikasi Public Relations Politik Luar Negeri Rumania - Prihartadi, Bambang; Ariyani, Nafiah (HK-Publishing, 2023)
AbstractPresident Klaus Werner Iohannis (KWI) implements strategic planning Public Relations for Romanian Foreign Policy (RFP). The obstacle of implementing RFP is the opposition from right and left populists using the issue of Euroscepticism. This paper will explain communications PR to overcome Euroscepticism and answer questions: How does President KWI uses communications PR for RFP?, How is Presiden KWIâ€™s communications? andÂ what step of communications is used by Romanian Government? To encounter Euroscepticism, KWI does communications PR by means of electronic media, printed media, and new media. Theoretical framework used is â€™â€™Strategic Planning for Public Relations 5th Editionâ€: phase one formative research; phase two strategy; phase three tactics; and phase four evaluative research. In this paper, communications PR uses Laswellâ€™s concept of communications: â€™Who, Says What, In what Channel, to Whom dan with What effect. KWI uses communications PR for foreign policy for Romanian and EU citizens. Lack of understanding the importance of being the EU member will improve Euroscepticism. This situation is taken advantage by right and left populists in Rumania and EU countries who are anti-EU integration. Therefore, Ministry of Foreign Affairs Romania together with other Ministries or government institutions have communications PR of foreign policy.Keywords: Communications Public Relations,Â Romania Foreign Policy, European Union, and Euroscepticism.Â Â AbstrakPresiden Klaus Werner Iohannis (KWI) melakukan strategi perencanaan komunikasi PR Politik Luar Negeri (Pollugri). Tantangannya adalah kelompok populis kanan/kiri yang menggunakan isu Euroskeptisisme. Paper akan menjelaskan komunikasi PR Pollugri dalam menghadapi Euroskeptisisme. Paper ini, menjawab pertanyaan tentang bagaimana Presiden KWI melakukan komunikasi PR pollugri? Seperti apa komunikasi PR tersebut? Apa langkah KWI dalam melaksanakan komunikasi PR? Untuk menghadapi Euroskeptisisme, KWI melakukan komunikasi PR Pollugri yaituÂ melaluiÂ media elektronik, cetakÂ dan media baru. Landasan teori yang diterapkan yaitu â€˜â€™Strategic Planning for Public Relations 5th Editionâ€Â yaituÂ Phase one Formative Research; Phase Two Strategy; Phase Three Tactics; dan Phase Four Evaluative Research. Komunikasi PR, menggunakan konsep komunikasi dari Laswell yaitu â€˜â€™Who, Says What, In what Channel, to Whom dan with What effect. Rumania menerapkan komunikasi PRÂ kepada WN Rumania dan WN UE. Tujuan komunikasi PR Pollugri adalah untuk mendapatkan dukungan WN (warga negara) Rumania dan WN UE. Kurangnya pemahaman pentingnya Rumania menjadi anggota UE dapat menumbuhkan Euroskeptisisme. Keadaan tersebut dimanfaatkan oleh kelompok anti-UE baik di Rumania dan di negara-negara UE. Kementerian Luar Negeri bersama sama dengan kementerian/lembaga terkait secara serempak melakukan komunikasi PR kebijakan pro UE.Â Â Kata kunci: Komunikasi PR (Public Relations),Â Politik Luar Negeri Rumania, Uni Eropa, dan Euroskeptisisme.